From Naples to Paris - Carlisi, Lydia (2023)
This study investigates the reception of partimento at the Paris Conservatoire between its foundation (1795) and 1840. The circulation of partimento in France during the 19th century is evinced by several sources, although, the use of partimenti in teaching at the Conservatoire has never been explored in depth. The Conservatoire initially emulated institutions such as the Neapolitan Conservatori, with the goal of producing French musicians and singers as successful as their Italian colleagues. Drawing on archival documents, manuscripts, and printed manuals, the teaching at the Conservatoire is reconstructed and the elements of partimento in these sources explored; the teaching of harmonie and accompagnement are also examined.